Structure of campus network based on reconfigurable architecture - Hu-sheng YUAN; Hua FENG; Hui LI; Zhi-bin ZHONG; Kai PAN (Tongxin xuebao)
Because of the petrifaction of the existing network,it is difficult to achieve the controllability,adaptability and expansibility in current structure.Simultaneously,in order to have better campus network services in teaching,researching and studying,a new structure based on reconfigurable architecture for campus network was designed based on service set handling capacity of various kinds of business in reconfigurable network as the central idea.After the evolution from tradition to flat structure,a more condensed structure was proposed by adopting virtualization technology on switches and routers.It has the advantages of high performance,high reliability,manageability and augmentability.